Honduras : Selected Issues and Analytical Notes. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Selected Issues paper uses efficiency frontiers for benchmarking of social spending in Honduras. The results reveal significant room to improve public health and education spending efficiency with potentially large fiscal savings. From an input-oriented point of view, Honduras performs poorly in education and health spending efficiency. From an output-oriented point of view, health spending efficiency appears to be in line with regional comparators, while there is room to improve efficiency in secondary education. In health and education spending, the priority is to tackle the disconnection between compensation benefits and labor productivity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet